TEX and LATEX - Marić, Filip (Infotheca - Journal for Digital Humanities, 2024)
This paper will present the document preparation systems TEX and LATEX. Documents created by these systems have very high aesthetic quality. Systems are mainly used for the production of technical and scientific documentation and are de facto standard for the communication and publication of scientific documents. Both systems are available as free software.